Self-selective van der Waals heterostructures for large scale memory array - Linfeng Sun (Nature Portfolio, 2019)
Designing large-scale crossbar arrays for energy efficient neuromorphic computing systems remains a challenge. Here, the authors propose Van der Waals (h-BN/graphene/h-BN) self-selective memory design able to combine, in the same cell, non-volatile and volatile behaviors with negligible sneak current.